Determination of metals in herbal products using inductively coupled plasma mass spectrometry (ICP-MS) - De Vera, Joan S. (Institute of Chemistry, College of Science, University of the Philippines Diliman, 2013)
Plants and products derived from them are known to be susceptible to elemental contamination hence, it is only important that these contaminants be monitored. In this study, trace concentrations of Cr, Cd, Sn and Pb in herbal products were simultaneously determined using a microwave-assisted digestion for the sample pre-treatment and inductively coupled plasma mass spectrometry (ICP-MS) for the elemental detection. Results generated from this study have shown that elemental contamination at trace levels is indeed possible in herbal products.